The etho-poietic of the parable of the good Samaritan (Lk 10:25-37). The ethics of seeing in a culture of looking the other way - Zimmermann, Ruben (Verbum et ecclesia, 2008)
Within a culture of "Looking the Other way" there are not only empirically ascertainable reasons why help is not given in acute emergency situations, there is also a "Theory of Not-Helping" that attempts to demonstrate argumentatively why it may even be better not to help. According to the article, the parable of the "good Samaritan" invites us, however, to "look closely". Four invitations of the text are developed, each with an emphasis on ethics: 1) The narrated Samaritan (The appeal structure of ethics); 2) The touched Samaritan (Ethics in the Context of Love); 3) The partisan Samaritan (Universal ethos of helping - or: Ethics of open partisanship); 4) The charitable Samaritan (Social ethics instead of ethics of conscience).